Optimization of Density of Sugar Beet (Beta vulgaris L.) Production Quotas by Pointwise Geostatistic Methods - Nagy, Ildikó; Tamás, János (Acta Agraria Debreceniensis, 2005)
The regional distribution of the Hungarian sugar beet production quotas was developed by the conventional concurrency relationships. In our research we analyzed 320 sectors of 9 factories with geostatistic methods in a GIS environment. The applied researches of spatial mean, spatial deviation, deviational ellipse have been introduced by us in this speciality. We used two different methods in our optimization inquiries, where the spatial segment of the standard deviational ellipse was based on a more robust preliminary data processing solution, and this is why it is a less parametricable method. The inquiry of the spatial buffer zones in production sectors ensures an obvious optimization possibility. We considered the supply route distances in both cases as a modeling boundary condition. Our results show that we introduced an effective decision making method to the occurent replanning of the production sectors with the pointwise density inquiries and the geometric analogy that was fitted to it.